Wind and whirlwind : utopian and dystopian themes in literature and philosophy - Heller, Agnes (Religious Studies, Theology and Philosophy E-Books Online, Collection 2019, ISBN: 9789004390898., 2019)
In Wind and Whirlwind the great philosopher Ágnes Heller and social scientist Riccardo Mazzeo explain the pros and cons of utopias and dystopias as they are described in literary works and their relevance to understand the world we live in and the hidden consequences of apparently appealing life trajectories.